The utilization of Malaysian local bentonite as an extender and free water controller in oil-well cement technology - Samsuri, Ariffin; Junin, R.; Osman, A. M. (2001)
This paper presents the result of experimental studies for Malaysian bentonite from Sabah (Lahad Datu and Tawau areas) application in oil-well cementing as compared to world wide commercially used Wyoming bentonite of USA. Samples were dried, grounded and sieved into particle size of 75Î¼m. The experiments include XRD & XRF techniques to determine the chemical compositions and mineralogical contentc of bentonite. Methylene blue tests were carried out to estimate the value of cation exchange capacity (CEC) in order to determine the approximate montmorillonite content. In the cement performance tests, class-G cement slurry mixed with bentonite in the range of 2%-6% BWOC. The cement slurries were tested in accordance of API Specification 10. Dry and wet treatment processes were also conducted for the Malaysian bentonite to upgrade its performance. From laboratory investigations, it showed that Malaysian bentonite has less content of montmorillonite mineral and more impurity materials such as quartz, kaolinite, illite, muscovite and hematite, while Wyoming bentonite considered as high-quality bentonite. Malaysian bentonite has low values of CEC which had been improved after treatment processes. Malaysian bentonite has low degree of swelling. The free water of the cement slurry increased with the increase of bentonite concentrations as compared to Wyoming bentonite. On the other hand, after treatment processes, the free water decreases in the cement slurry with bentonite concentrations increased. The Lahad Datu's bentonite had lowered slurry density after the treatments than the Tawau's bentonite.